(untitled) (Моделювання, керування та інформаційні технології, 2020)
The goal of this research is to create a mathematical model of political parties supporters redistribution. In this work it is done via creating a system of differential equation for the case when society has two political parties and non-partisan citizens. In the second part, the model is generalized for the case of n political parties or groups.